2021
DOI: 10.3389/fcvm.2021.653991
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Sclerosis as an Important Predictor of Long-Term Mortality in Patients With Carotid Atheromatous Plaque Requiring Carotid Endarterectomy

Abstract: Background: A strong association between aortic valve sclerosis (AVSc), the earliest manifestation of calcific aortic valve disease, and atherosclerosis exists. The aim of the study was to evaluate the predictive capabilities of AVSc on long-term all-cause mortality, in patients requiring carotid endarterectomy (CEA).Methods and Results: 806 consecutive CEA patients were enrolled. Preoperative echocardiography was used to assess AVSc. Computed tomography angiography was applied for plaque characterization. Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In addition, the diversity within our patient population, encompassing various age groups, sexes, and comorbidities, strengthens the potential relevance of our findings to a broader spectrum of patients with AVSc. Furthermore, our findings are consistent with those of previous research, 3,4,35–37 which reinforce the notion that AVSc is associated with adverse cardiovascular outcomes. By continuing to unravel the intricate molecular mechanisms underlying this condition, our work may contribute to improved diagnosis and screening, offering potential benefits to patients affected by nonstenotic aortic valve fibro-calcification remodeling.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the diversity within our patient population, encompassing various age groups, sexes, and comorbidities, strengthens the potential relevance of our findings to a broader spectrum of patients with AVSc. Furthermore, our findings are consistent with those of previous research, 3,4,35–37 which reinforce the notion that AVSc is associated with adverse cardiovascular outcomes. By continuing to unravel the intricate molecular mechanisms underlying this condition, our work may contribute to improved diagnosis and screening, offering potential benefits to patients affected by nonstenotic aortic valve fibro-calcification remodeling.…”
Section: Discussionsupporting
confidence: 93%
“…Previously, the results of a meta-analysis on more than 30 studies, which included 10537 patients with AVSc and 25005 controls, showed that the presence of AVSc is associated with coronary artery disease, stroke, and cardiovascular mortality 8 . Indeed, the prevalence of AVSc in patients with CAD is about 45% and even higher (> 60%) in patients with carotid atherosclerosis and after coronary or carotid revascularization these patients had increased overall mortality compared with patients without AVSc 10,11 . Moreover, in patients who underwent coronary artery bypass graft (CABG), the 90-day survival was significantly lower in the AVSc group and the addition of AVSc to the EuroSCORE II improved the stratification of these high-risk patients 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of our previous studies demonstrated that the atherosclerosis risk factors, such as age, hypertension, dyslipidemia, and diabetes mellitus, are associated with AVSc 7 , while epidemiological studies suggested that AVSc is a predictor of both all-cause and cardiovascular mortality 8,9 . Thus, it is not surprising that atherosclerotic diseases (e.g., carotid or coronary atherosclerosis) and AVSc often coexist in the same subject 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, P2RY2 stimulation could be implemented at the earliest stage of CAVS (i.e., aortic valve sclerosis; AVSc), which is an essential step toward the end-stage disease [ 6 , 25 ]. AVSc is an echocardiographic finding not well understood, which remains a very controversial topic considering it has no clinical symptoms but is linked to increased cardiovascular risk and associated mortality [ 26 , 27 , 28 ]. Taken together, these data suggest that P2RY2 selective activation should be further investigated as a pharmacological target for the prevention of CAVS progression, acting on both calcification and myofibroblastic activation of VICs.…”
Section: Discussionmentioning
confidence: 99%